Understanding Muslim Assimilation in America: An Exploratory Assessment of First & Second-Generation Muslims Using Segmented Assimilation Theory. Issue 2 (2nd April 2020) - Asfari, Amin; Askar, Anas
Abstract: Immediately following the attacks of 9/11 in New York, mainstream media outlets echoed the notion of Muslims as strangers who are unable to assimilate into American culture. The purported difficulty in the assimilation of Muslims in America was linked with their religious affiliation, an indelible marker of their ideology, and one that supersedes any national identity. Given the paucity of research on the assimilation of Muslims in America, this paper sought to explore if-and-how this group is assimilating into American culture. Utilizing a mixed-method design, we conducted focus groups, followed by a multi-state survey. Using segmented assimilation theory, we found evidence that Muslims with higher educational attainment and household incomes are well-assimilated. We also found that respondents who identify themselves strongly as Muslim are less likely to assimilate, preferring instead to maintain close in-group ties. We discuss the implications of these findings in greater detail.